Case Report: A case of spinal muscular atrophy with extensively drug-resistant Acinetobacter baumannii pneumonia treated with nebulization combined with intravenous polymyxin B: experience and a literature review - Cao, Bingqing; Cao, Ling (Frontiers in Cellular and Infection Microbiology, 2023)
This paper presents a case of nebulization combined with intravenous polymyxin B in a child with spinal muscular atrophy with extensively drug-resistant Acinetobacter baumannii pneumonia. Our work provides a reference for the treatment of children with extensively drug-resistant Acinetobacter baumannii pneumonia.